Franz J. Hinkelammert: The political-cultural option for the impoverished and the desire for God - Gallardo, Helio (2025)
This article starts from the fact that, currently, religiosities and religious institutions have a determining political impact in certain situations. Hinkelammert’s approach is taken up according to which the emancipatory political decisions offered by religious and nonreligious